Electrochemical properties and lithium-ion storage mechanism of LiCuVO4 as an intercalation anode material for lithium-ion batteries. Issue 2 (19th November 2014) - Li, Malin; Yang, Xu; Wang, Chunzhong; Chen, Nan; Hu, Fang; Bie, Xiaofei; Wei, Yingjin; Du, Fei; Chen, Gang
Abstract : LiCuVO4, as an intercalation-type anode, shows spontaneous coating behavior with Cu nanoparticles on the surface of Li3 VO4 after the 1st discharge. Abstract : LiCuVO4 with distorted inverse spinel structure is prepared by solid-state reaction and comprehensively examined as an intercalation anode material by means of cyclic voltammograms (CV), galvanostatic charge–discharge profiles, rate performance, and electrochemical impedance spectroscopy (EIS). LiCuVO4 shows a stable capacity of 447 mA h g −1 under 3–0.01 V at the current density of 200 mA g −1, and the capacity retention reaches 91% after 50 cycles. At high cutoff voltage, between 3 and 0.2 V, LiCuVO4 also delivers an average reversible capacity of 200 mA h g −1 at a current density of 2000 mA g −1, higher than the performance of the newly reported Li3 VO4 . Moreover, the lithium ion storage mechanism for LiCuVO4 is also explained on the basis of the ex situ X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) at different insertion/extraction depths. While being discharged to 0.01 V, LiCuVO4 decomposes into Li3 VO4, whose surface is coated by Cu nanoparticles spontaneously. Interestingly, Li ions are suggested to be inserted into Li3 VO4 in the subsequent cycles due to the intercalation mechanism, and Cu nanoparticles would not contribute to the reversible capacity. Our findings provide a strong supplemental insight into the electrochemical mechanism of the anode for lithium-ion batteries. In addition, LiCuVO4 is expected to be a potential anode material because of its low cost, simple preparation procedure, good electrochemical performance and safety discharge voltage.